2013
DOI: 10.1103/physrevlett.111.243005
|View full text |Cite
|
Sign up to set email alerts
|

High-Harmonic Probing of Electronic Coherence in Dynamically Aligned Molecules

Abstract: We introduce and demonstrate a new approach to measuring coherent electron wave packets using high-harmonic spectroscopy. By preparing a molecule in a coherent superposition of electronic states, we show that electronic coherence opens previously unobserved high-harmonic-generation channels that connect distinct but coherently related electronic states. Performing the measurements in dynamically aligned nitric oxide (NO) molecules we observe the complex temporal evolution of the electronic coherence under coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 38 publications
3
88
0
Order By: Relevance
“…Time-domain studies of electrons in atoms, molecules, and the condensed phase offer new approaches to understanding electronic structure and electronic correlations (see, e.g., [1][2][3][4][5][6]). Electronic wave packets have been measured in the valence shell of atomic ions using transient absorption [7,8] or sequential double ionization [9,10] and in the valence shell of neutral molecules using high-harmonic spectroscopy [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Time-domain studies of electrons in atoms, molecules, and the condensed phase offer new approaches to understanding electronic structure and electronic correlations (see, e.g., [1][2][3][4][5][6]). Electronic wave packets have been measured in the valence shell of atomic ions using transient absorption [7,8] or sequential double ionization [9,10] and in the valence shell of neutral molecules using high-harmonic spectroscopy [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Note that although focal-volume averaging will reduce the averaged excitation fraction, 4% is considerably larger than the number of 0.2% reported in Ref. [8]. In Ref.…”
Section: Discussion Of Numerical Resultsmentioning
confidence: 63%
“…Recently, we demonstrated that the HHG process can map out electronic coherences with high sensitivity [8]. The basic principle of the detection process is a cross channel of the HHG process, that coherently connects different electronic states (see Fig 1a).…”
mentioning
confidence: 99%
See 2 more Smart Citations